Understanding the role of Si alloying on the structural, mechanical, wear and high temperature oxidation behavior of CrFeNiTiX (X=Si) high entropy alloys - Nagarjuna, Cheenepalli; Lee, Hansung; Dewangan, Sheetal Kumar; Rao, K. Raja; Pillai, Gokul M.; Kumar, Vinod; Ahn, Byungmin (Journal of Materials Research and Technology, 2024)
The present study explores the structural, mechanical, wear, and high temperature oxidation behavior of CrFeNiTiX(X = Si) high entropy alloys (HEAs) processed by powder metallurgy. The results revealed the formation of single-phase body centered cubic (BCC) structure in both alloys after 30 h of milling. After sintering, the Si added HEA exhibited an increased fraction of the BCC phase and promotes the formation of Cr3Si phases. The addition of Si enhances the microhardness (1200–1330 HV), ultimate compressive strength (1400 ± 80 MPa to 1700 ± 50 MPa), nanohardness (12–15.7 GPa) and elastic modulus (12–15.7 GPa) attributed to the solid solution strengthening resulting from the lattice distortion. The Si added HEA showed reduced specific wear rates under all the applied loads, attributed to increased hardness and surface oxidation, which resists plastic deformation. Moreover, the oxidation resistance was enhanced by the addition of Si up to 800 °C, attributed to the formation of a protective oxide layer on the surface. However, at 900 °C, the resistance decreased due to spallation of the oxide layer. Therefore, the present study demonstrates the addition of Si improves the hardness, wear resistance, and oxidation resistance, making HEAs are suitable for high-temperature and wear-resistant applications.
Keywords: Body-centered-cubic phase; Body-centred cubic; Cubic structure; High entropy alloys; High temperature oxidation Behavior; Lattice distortions; Mechanical; Single phasis; Solid solution strengthening; Ultimate compressive strength; High-entropy alloy; Microstructure; Oxidation resistance; Powder metallurgy; Wear resistance